Age‐related differences in self‐report and objective measures of cognitive function in older patients prior to chemotherapy. Issue 2 (8th December 2021) - Utne, Inger; Løyland, Borghild; Grov, Ellen Karine; Rasmussen, Hege Lund; Torstveit, Ann Helen; Paul, Steven M.; Ritchie, Christine; Lindemann, Kristina; Vistad, Ingvild; Rodríguez‐Aranda, Claudia; Miaskowski, Christine
Abstract: Aim: Evaluate for differences in demographic and clinical characteristics and subjective and objective measures of cognitive function (CF) between younger older adults (YOA, 60–69 years) and older adults (OA, ≥70 years). Design: Cross‐sectional. Methods: Older oncology patients ( n  = 139) completed subjective (Attentional Function Index, European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC) CF scale) and objective (Montreal Cognitive Assessment, Trail Making Test (TMT) A & B) measures of CF prior to chemotherapy. Data were analyzed using parametric and nonparametric tests. Results: No differences were found between the two groups for any of the subjective or objective CF measures, except that OA patients had higher TMT B scores. Compared with the general population, OAs had significantly higher EORTC CF scores and YOAs had significantly worse scores for all of the objective tests. Clinically meaningful difference between group differences was found for the TMT B test.